New species of Lebania (Diptera: Limoniidae) from mid-Cretaceous amber of northern Myanmar. (December 2019) - Men, Qiulei; Hu, Zhengkun; Mu, Dan
Abstract: Three new species of Lebania Podenas and Poinar, 2001, Lebania podenasi sp. nov., Lebania hukawngensis sp. nov. and Lebania pilosa sp. nov. are described and illustrated from the mid-Cretaceous amber of northern Myanmar. A key to all recorded species in this genus is provided. These three new species represent the second record of Lebania species from Burmese amber, one of which represents the first record of a female specimen for this genus.